(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this work, we consider a class of homogeneous irreducible discrete states Markov process , taking values in a partition of some topological space . Using a notion of fractional state, we introduce a general transformation such that remains a Markov process. This general transformation includes also lumpability. Infinite kinds of this expanded Markov chain can be constructed, however lumped Markov chains are finite or may not exist . Using general transformation and fractional states, we give a necessary and sufficient condition under which the transformed process remains still a Markov chain